Are infections in children with juvenile idiopathic arthritis more frequent than in healthy children? A prospective multicenter observational study - Udaondo, Clara; Núñez Cuadros, Esmeralda; Murias, Sara; Remesal, Agustin; Alcobendas, Rosa; Guerrero, Concepción; Guillen-Martin, Sara; Escuredo, Marta; Aleo, Esther; Alonso, Daniel; Tagarro, Alfredo; De Santiago, Eloisa; et al. (Frontiers in Pediatrics, 2022)
Children with JIA may have a higher risk of infection. Our objectives are to describe and compare infection rates in JIA patients vs non-JIA counterparts. A prospective, multicenter observational study was performed in Spain from 01/2017 to 06/2019. JIA patients from 7 participating hospitals and children without JIA (siblings of JIA patients, and non-JIA children from primary health centers) were followed up with quarterly questionnaires recording infection episodes. Tuberculosis, Herpes Zoster, and infections requiring hospital admission were considered severe infections. Rate of infection (episodes/patient/year) was compared using a Generalized Estimating Equations Model. A total of 371 children (181 JIA and 190 non-JIA) were included. Median age was 8.8years (IQR 5.5 – 11.3); 75% of JIA patients received immunosuppressive treatment (24% methotrexate, 22% biologic, 26% both). 667 infections were recorded, 15(2.2%) considered severe. Infection rate was 1.31 (95%CI 1.1 – 1.5) in JIA and 1.12 (95%CI 0.9 – 1.3) in non-JIA participants (p0.19). Age <4 years increased 2.5 times infection rate (2.72 vs. 1.12, p<0.001) in both groups. The most frequent infection sites were upper respiratory (62.6% vs. 74.5%) and gastrointestinal (18.8%vs 11.4%). There were no differences in severe infections (2.5%vs 2%, p0.65) among groups. In JIA children, younger age and higher disease activity (JADAS71) were associated with a higher infection rate. We found no differences in infection rate and severity between patients with and without JIA. Most infections were mild. Age below 4 years increased infection risk in both groups. Higher disease activity was associated with a higher infection rate.